Psychological Well-Being in Obese Inpatients with Ischemic Heart Disease at Entry and at Discharge from a Four-Week Cardiac Rehabilitation Program - Manzoni, Gian Mauro; Cribbie, Robert; Villa, Valentina; Arpin-Cribbie, Chantal; Gondoni, Luca; Castelnuovo, Gianluca (Frontiers in Psychology, 2010)
The purposes of this observational pre-post study were twofold: 1- to evaluate psychological health in obese patients with ischemic heart disease (IHD) at admission to cardiac rehabilitation (CR) and 2 - to examine the effectiveness of a four-week CR residential program in improving obese patients’ psychological well-being at discharge from CR. A sample of 177 obese patients completed the Psychological General Well-Being Inventory (PGWBI) at admission to the CR program and at discharge. The equivalence testing method with normative comparisons was used to determine the clinical significance of improvements after having established that baseline mean scores on the PGWBI scales were significantly lower than normal means. Results show that patients scored equally or better than norms on many PGWBI dimensions at admission to CR but scored significantly worse on Global Score, Vitality and Self-control. At discharge, mean scores that were impaired at baseline returned to normal levels at the more conservative equivalence interval. A four-week CR program was thus effective in improving obese patients’ psychological well-being. The equivalence testing method allowed to establish the clinical significance of such improvement.